2010
DOI: 10.1021/bi1004409
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of the Green Tea Polyphenol (−)-Epigallocatechin Gallate−Transthyretin Complex Reveals a Novel Binding Site Distinct from the Thyroxine Binding Site,

Abstract: Amyloid fibril formation is associated with protein misfolding disorders, including neurodegenerative diseases such as Alzheimer's, Parkinson's, and Huntington's diseases. Familial amyloid polyneuropathy (FAP) is a hereditary disease caused by a point mutation of the human plasma protein, transthyretin (TTR), which binds and transports thyroxine (T(4)). TTR variants contribute to the pathogenesis of amyloidosis by forming amyloid fibrils in the extracellular environment. A recent report showed that epigallocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 59 publications
6
101
0
Order By: Relevance
“…S-11). In conclusion, these and previously published results point to EGCG as a generic binder [34][35][36][37][38][39][40][41][42] and modulator 41,42 of protein structure.…”
Section: Egcg Binding Promotes As Compactionsupporting
confidence: 79%
“…S-11). In conclusion, these and previously published results point to EGCG as a generic binder [34][35][36][37][38][39][40][41][42] and modulator 41,42 of protein structure.…”
Section: Egcg Binding Promotes As Compactionsupporting
confidence: 79%
“…Concerning EGCG, it does not compete with T 4 for the binding to TTR [13] therefore the stabilization effect of EGCG on TTR is independent from the stabilization effect of T 4 and additionally strengthens the effect of T 4 [21]. Furthermore, the characterization of the EGCG-TTR V30M complex revealed that EGCG binds at the surface of TTR molecule, in a region involving amino acid residues at the interface of both dimmers, promoting tetramer stabilization [21].…”
Section: Discussionmentioning
confidence: 97%
“…3), further indicated that EGCG directly bound and stabilised TTR tetramer in vitro, and induced TTR oligomerisation in cells 34 . The pharmaceutical mechanism of EGCG curing of yeast prions [PSI] could be via stabilisation of the native prion domain Sup35 as well 35 .…”
Section: Attenuation Of Tdp-43 Degradation By Egcgmentioning
confidence: 93%